PLURALISM OF THE UNDERSTANDING OF LAW: LEGISTIC AND LEGAL APPROACH - Ashuroxunova Iroda Tohir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article talks about the approaches of various legal scholars to the understanding of law, as well as the important aspects of pluralism in the understanding of law, the natural approach to the understanding of law, and the positivist approach.